Metody consensusu w systemach wspomagających podejmowanie decyzji - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Consensus Methods in Decision Support Systems, 2008)
A consensus methods for Decision Support Systems are presented in this article. Consensus methods are one of the methods for solving conflicts in distributed systems and so in Decisions Support Systems. A Decision Support Systems problem and consensus methods nature are described in the article. A definition of the distance function, which is an element of consensus, definition of consensus functions and postulates for consensus functions are presented in this article. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 95-106